Genesis history of iron ore from Mesoarchean BIF at the Wodgina mine, Western Australia. Issue 1 (2nd January 2017) - Teitler, Y.; Duuring, P.; Hagemann, S. G.
ABSTRACT: Several iron-ore deposits hosted within Mesoarchean banded iron formations (BIFs) are mined throughout the North Pilbara Craton, Western Australia. Among these, significant goethite±martite deposits (total resources >50 Mt at 55.8 wt% Fe) are distributed in the Wodgina district within 2 km of the world-class pegmatite-hosted, tantalum Wodgina deposits. In this study, we investigate the dominant controls on iron mineralisation at Wodgina and test the potential role of felsic magma-derived fluids in early alteration and upgrade of nearby BIF units. Camp-scale distribution and geochemistry of iron ore at Wodgina argue against any significant influence of identified felsic intrusions in the upgrade of BIF. Whereas, the formation of BIF-hosted goethite±martite iron ore at Wodgina involves: (i) early ( ca 2950 Ma) metamorphism of BIF causing camp-scale recrystallisation of pre-existing iron oxides to form euhedral magnetite, with local enrichment to sub-economic grades (∼40 wt% Fe) within or proximal to metre-wide, bedding-parallel shear zones, and (ii) later supergene lateritic enrichment of the magnetite-bearing BIF and shear zones, forming near-surface goethite±martite ore. The supergene alteration sequence includes: (i) downward progression of the oxidation front and replacement of magnetite by martite, (ii) local development of silcrete at ∼40 m below the modern surface caused by the lowering of the water-table, (iii) intensive replacement of quartz by goethite, resulting in the goethite±martite ore bodies at Wodgina, and (iv) late formation of ferricrete and ochreous goethite. Goethitisation most likely took place within the hot and very wet climate that prevailed from the Paleocene to the mid-Eocene. Goethite precipitation was accompanied by the incorporation of trace elements P, Zn, As, Ni and Co, which were likely derived from supergene fluid interaction with nearby shales. Enrichment of these elements in goethite-rich ore indicates that they are potentially useful pathfinder elements for concealed ore bodies covered by trace element-depleted pedogenic silcrete and siliciclastic rocks located throughout the Wodgina mine.